BUDAYA HARMONISASI HINDU–MUSLIM DI PURA BHUR BWAH SWAH SERAYA-BUKIT KARANGASEM: ANALISIS EMPAT INDIKATOR MODERASI BERAGAMA - Joni Artha; I Nyoman Ariana Guna; I Made Wirajana; Erika Gunawati; I Gede Sudha Cahyana (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2026)
This study examines the practice of interfaith interaction between Hindu and Muslim communities in Seraya-Bukit Village, Karangasem Regency, with a focus on the participation of Muslim semeton in arranging offerings at Bhur Bwah Swah Temple. The study used a qualitative approach through in-depth interviews with Jro Mangku I Made Kembar and I Gusti Ayu Mas Sumatri, conducted on January 7, 2026, and analyzed from the perspective of social theology and religious moderation. The results show that the arrangement of offerings by Muslim semeton in the month of Safar, coinciding with the third full moon, is interpreted as a cultural-religious expression of gratitude, not as an Islamic worship practice. This practice takes place while maintaining theological boundaries and respecting Hindu sacred space, and represents the value of menyama braya as a basis for social harmony. This study concludes that religious moderation in Seraya-Bukit Village exists as a social praxis rooted in Balinese local wisdom and supported by regional policies, thus enabling harmonious interfaith relations without blurring each person's religious identity.